Empirical Investigation of Lean Six Sigma Enablers and Barriers in Indian MSMEs by Using Multi-Criteria Decision Making Approach. Issue 3 (3rd July 2022) - Singh, Mahipal; Rathi, Rajeev
Abstract: Lean Six Sigma (LSS) is an inclusive approach based on the concept of waste and variation reduction to achieve quality and sustainability. The successful adoption of any approach depends upon the awareness and readiness measures of a particular one. This paper contributes toward Micro-Small and Medium Enterprises (MSMEs) to adopt a comprehensive LSS approach in their existing system through the identification, analysis, and prioritization of LSS enablers and barriers. In the present study, 25 enablers and 21 barriers of LSS adoption are identified through literature review and are validated by using questionnaire-based survey. The screened enablers and barriers are further formulated into logical groups using factor analysis. These formulated groups are prioritized through Analytical Hierarchy Process (AHP) and compared the obtained results with the fuzzy decision-making trial and evaluation laboratory (Fuzzy-DEMATEL). The result reveals that among the main group of enablers, "management-based factor" is the top-ranked followed by "training- and education-based factor" and "technology-based factor" with AHP weights 0.4008, 0.2742, and 0.1465 respectively. On the other hand, among the main groups of barriers, "training and education based factor" is at first rank trailed by "management-based factor" with AHP weights 0.4780 and 0.2915 respectively. The outcomes of current research will facilitate the MSMEs to make a favorable environment toward the LSS approach for increasing productivity and profitability dynamics. An engineering manager can use this paper to enhance social sustainability through the incorporation of LSS approach in the communities where they work. Moreover, this study provides a guiding reference for practitioners and academicians to undertake similar nature of problems into other industrial sectors.